Estimation and Comparison of Anopheles maculipennis s.l. (Diptera: Culicidae) Survival Rates with Light-trap and Indoor Resting Data - MB Ghavami (Tehran University of Medical Sciences, 2005)
The main vector of malaria in Europe and Palearctic region is Anopheles maculipennis complex. In order to determine the survival rate of An. maculipennis s.l. this study was carried out in Garaboteh (Zanjan province, Iran) in July 2003. In this study anophelines were sampled for 31 consecutive days from five fixed animal shelters and five light traps. Out of 24481 collected An. maculipennis s.l., 19703 (80.48%) were female. Relative density of female anopheline with 95% CI was 74.25-78.48 and 49.16-52.36 in light traps (LT) and pyrethrum space spray catch (PSC), respectively. A significant difference was in mean parous rate in LT (0.46) and PSC (0.50) samples (P0.92) between parous and total females. Also there was significant correlation between nulliparous females and males in LT (r=0.96) and PSC (r=0.87) samples and with increasing anopheline abundance ratio of male/nulliparous significantly decreased (r=-0.35, P<0.05). Due to simplicity and feasibility of using graphical and parametric method, it can be placed in entomological surveys for monitoring parity, age structure and survival rate of vector anopheline in the world.